Healthcare-seeking behavior of patients with epileptic seizure disorders attending a tertiary care hospital, Kolkata - Abhik Sinha; Sarmila Mallik; Debasish Sanyal; Prasenjit Sengupta; Samir Dasgupta (Wolters Kluwer Medknow Publications, 2012)
Introduction : Neurological diseases are very important causes of prolonged morbidity and disability, leading to profound financial loss. Epilepsy is one of the most important neurological disorders Healthcare seeking by epilepsy patients is quite diverse and unique. Aims and Objectives: The study was conducted among the epilepsy patients, to assess their healthcare-seeking behavior and its determinants. Materials and Methods: Three hundred and fifteen epilepsy patients, selected by systematic random sampling, in the neuromedicine outpatient department of a tertiary care hospital were interviewed with a predesigned, pretested, semi-structured proforma. Results and Conclusion: More than 90% sought healthcare just after the onset of a seizure. The majority opted for allopathic medicine and the causes for not seeking initial care from allopaths were ignorance, faith in another system, constraint of money, and so on. A significant association existed between rural residence and low social status of the patients with initial care seeking from someone other than allopaths. No association was found among sex, type of seizure, educational status of the patients, and care seeking. The mean treatment gap was 2.98 ± 10.49 months and the chief motivators were mostly the family members. Patients for anti epileptic drugs preferred neurologists in urban areas and general practitioners in rural areas. District care model of epilepsy was proposed in the recommendation.